Índice de integridade ecológica para ecossistemas lóticos da região nordeste do Rio Grande do Sul - Mazzoni, Aline Corrêa (My University, 2014)
The use of benthic macroinvertebrates has emerged as an important component to assessment of aquatic ecosystems biological integrity. Several indices based on benthic communities have been proposed in Brazil, demonstrating the need to expand the knowledge about the use of biotic communities in the assessment of the lotic ecosystems quality. This study aims to present a new biological index to examine the ecological integrity of mountain streams from Rio Grande do Sul, based on benthic macroinvertebrate communities and the conductivity measurement. The study was based on samplings performed during the period of 2002 to 2011, in 35 streams in the regions Campos de Cima da Serra and Encosta Superior Nordeste, including the cities of Antônio Prado, Cambara do Sul, Caxias do Sul, Itati, São Francisco de Paula, São Marcos and Três Forquilhas The data used in the Integrity Ecological Index (IEI) development included 88 samples and 1495 cases, and allowed the evaluation of the ecological amplitude of 38 taxa. The coefficient of variation was used to determine which physical and chemical measures are best to differentiate the water courses ecological quality. Linearized regression analysis (Stepwise) were performed to determine which physicochemical parameters show the best relation with the structure of the communities. The parameters conductivity and Chemical Index, indicated by this analysis, were used to estimate the ecological valence of taxa. The association between taxa (Euclidean distance) was used to determine the indicator groups. With the results of these analyzes was possible to assign scores to the macroinvertebrates and to the conductivity values, according to their indication on an environmental gradient. A classification system of ecological integrity was formulated, considering these scores, to indicate the degree of environmental impact in mountain streams of the studied region. When compared to the Chemical Index, the IEI showed a larger number of affected sites, demonstrating to be more sensitive in the assessment of ecological integrity. The IEI could be a useful tool to help managers assess environmental risk in mountain stream ecosystems. [resumo fornecido pelo autor]
O uso de macroinvertebrados bentônicos está estabelecido como um componente relevante na avaliação da integridade biológica de ecossistemas aquáticos. Diversos índices têm sido propostos no Brasil, demonstrando a necessidade da ampliação do conhecimento acerca do uso de comunidades bióticas na avaliação da qualidade de sistemas lóticos. Este estudo propõe um novo índice biológico para verificar a integridade ecológica de ecossistemas lóticos da serra nordeste do Rio Grande do Sul, baseado nas comunidades de macroinvertebrados bentônicos e na medida de condutividade. Como base, foram utilizadas coletas efetuadas entre 2002 e 2011, em 35 cursos d’água das regiões dos Campos de Cima da Serra e Encosta Superior Nordeste, incluindo os municípios de Antônio Prado, Cambará do Sul, Caxias do Sul, Itati, São Francisco de Paula, São Marcos e Três Forquilhas. Os dados utilizados para a elaboração do Índice de Integridade Ecológica (IIE) incluíram 88 amostras e 1495 casos, possibilitando avaliar a valência ecológica de 38 táxons. O coeficiente de variação foi utilizado para determinar quais medidas físico-químicas melhor diferenciam os cursos d’água, segundo a sua qualidade ecológica. Análises de regressão linearizada (Stepwise) foram realizadas para verificar quais parâmetros físico-químicos melhor inflenciam a estrutura das comunidades. Os parâmetros condutividade e Índice Químico, indicados por esta análise, foram utilizados para estimar a valência ecológica dos táxons. A associação entre os táxons (Distância Euclidiana) foi utilizada para determinar os grupos indicadores. Os resultados destas análises permitiram atribuir pontuações aos macroinvertebrados e aos valores de condutividade, conforme a sua indicação em um gradiente ambiental. Considerando essas pontuações, formulou-se um sistema de classificação da integridade ecológica para indicar o grau de impacto ambiental em ecossistemas lóticos da área estudada. Quando comparado ao Índice Químico, a aplicação do IIE evidencia um maior número de locais impactados, demonstrando maior sensibilidade na avaliação da integridade ecológica. O IIE pode ser uma ferramenta útil para auxiliar gestores na avaliação de risco ambiental nos ecossistemas lóticos da região. [resumo fornecido pelo autor]
Keywords: Ecossistemas - Rio Grande do Sul; Monitoramento biológico; Invertebrado; Biotecnologia